Effect of rosemary (Rosmarinus officinalis) extracts on the oxidative stability and sensory acceptability of soybean oil - Dias, Liara Silva [UNESP]; Menis, Michele Eliza Cortazzo [UNESP]; Jorge, Neuza [UNESP] (Wiley, 2014)
Background: Plant extracts have b een used as an alternative to the use of synthetic antioxidants in order to preserve oils fromoxidative degradation. Additionally, these extracts add special flavors and aromas to the food. Thus, the objective of this studywas to evaluate the effect of hydroethanolic extracts of fresh and freeze-dried rosemar y in the oxidative stability of soybean oilunder accelerated storage in an oven. Results: The application of the extracts in the oil showed that that freeze-dried extract was better in reducing the formation ofoxidation products, showing 8.6 meq kg−1of peroxides after 20 days of storage. On the other hand, the mixture of the naturalextract with t-butylhydroquinone conferred better oxidative stability index until the 20th day, 9.7 h. Both extracts prevented theloss of tocopherol, not d iffering between each other (P > 0.05), and present approximately 505 mg kg−1of residual tocopherols.The sensory evaluation revealed that consumers accepted equally the oils added and not added of the rosemary extracts. Conclusion: The extracts are therefore potential sources of natural antioxidants and they would be well accepted by consumersif applied by the food industry to replace synthetic antioxidants.
Keywords: antioxidante natural; estabilidade oxidativa; tocoferóis; vegetable oils; natural antioxidant; oxidative stability; tocopherols